ROLE OF EMPATHY AND EMOTIONAL INTELLIGENCE IN THE PREVENTION OF BULLYING AMONG HIGH SCHOOL STUDENTS - Rybinska, Yuliia; Kolesnykova, Ani (Collection of scientific papers «ΛΌГOΣ», 2025)
Bullying is a serious problem affecting schoolchildren and adolescents around the world. It comes in many forms, from physical violence to emotional and psychological bullying. This paper will examine the signs of bullying, its consequences, and ways to prevent it. We will discuss how communication and a supportive environment can help combat this problem. Teaching children empathy and the active intervention of others play a key role in preventing bullying. Victim support and cooperation with professionals are also important aspects that can help to address bullying and create a safe, educational environment.